2013
DOI: 10.1007/s11626-013-9623-3
|View full text |Cite
|
Sign up to set email alerts
|

B16/F10 tumors in aged 3D collagen in vitro simulate tumor growth and gene expression in aged mice in vivo

Abstract: Although the incidence of cancer rises with age, tumor growth is often slowed in older hosts. The B16/F10 melanoma cell line is commonly used in murine models of age-related tumor growth suppression. We wished to determine if the growth pattern and gene expression of B16/10 tumors grown in aged mice could be simulated in 3D collagen matrices derived from aged mice. Outcome measures were tumor size in vitro and gene expression of the key growth regulatory molecules: growth hormone receptor (GHR), IL-10Rβ, IL-4R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Moreover, GHRs have been demonstrated in human and murine melanoma cells [20, 23]. We therefore examined the effects of GH on cultured melanoma cells.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, GHRs have been demonstrated in human and murine melanoma cells [20, 23]. We therefore examined the effects of GH on cultured melanoma cells.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, we and others have established that 3D gels polymerized from collagen extracted from young and aged animals induce differential cellular responses that reflect tissue aging (Jiang et al 2000; Bartling et al 2009; Damodarasamy et al 2010). Moreover, aged collagenous ECM in vitro provides an environment that can simulate pathologic responses in vivo (Bentov et al 2013). …”
Section: Resultsmentioning
confidence: 99%
“…Collagenous ECM extracted from tail tendons and polymerized into 3D gels provides an ideal model to study the effect of specific ECM components on cell behaviors (Bartling et al 2009; Leventhal et al 2009). Three-dimensional gels made from collagen extracted from aged animals are highly useful tools to study the effects of aged ECM on cell behaviors in vitro, which are relevant to cell-ECM interactions in vivo (Bentov et al 2013). In this context, we found that, compared to young collagen gels, aged collagen gels elicited significantly greater proliferation of three distinct prostate epithelial cell lines: PEC, BPH-1, and LNCaP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation